RESPON PEMBERIAN ABU SABUT KELAPA DAN PUPUK KCL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH - Yanema Waruwu (Universitas Nias Raya, 2025)
Shallot (Allium ascalonicum L.) is one of the leading vegetable commodities that has long been cultivated intensively by farmers. The application of coconut husk ash and KCl fertilizer in shallot cultivation is considered necessary to enhance its productivity. This study aimed to evaluate the response of coconut husk ash and KCl fertilizer on the growth and yield of shallot. The research was conducted at the Agrotechnology Practicum Field, located in Nanowa Village, Teluk Dalam District, South Nias. The experiment was arranged in a factorial randomized block design (RBD), with each factor consisting of three treatment levels and three replications, resulting in nine treatment combinations. Observed parameters included plant height, number of leaves, number of tillers, bulb weight, and bulb number. Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test. The LSD results showed that the interaction of coconut husk ash and KCl fertilizer had no significant effect on either the growth or yield parameters of shallot. The combination treatments of coconut husk ash and KCl fertilizer did not significantly influence shallot performance. The highest values were obtained at the treatment level A0K0 (without coconut husk ash + 300 kg/ha KCl).